Treatment of Teeth with Open Apices and Apical Pathology with MTA Cement used as Orthograde Root Filling Material - Chhabra, Harpreet Singh; Agarwal, Satyendra; Bhardwaj, Kshiti (Journal of Orofacial Research, 2013)
A major problem in performing endodontics in immature teeth with necrotic pulp and wide open apices is obtaining an optimal seal of the root canal system. The aim of the procedure is to remove periapical pathology and to limit bacterial infection to create an environment conductive for the production of mineralized tissue barrier or root end formation at the immature root end, i.e. apexification. Calcium hydroxide is commonly used for this purpose. Mineral trioxide aggregate (MTA) has been proposed as a potential material to create an apical plug at the end of the root canal system and facilitate a favorable environment for apexification. MTA is a powder that consists of fine hydrophilic particles that set in the presence of moisture. The setting time of MTA is less than 4 hours. The major compounds of MTA are tricalcium silicate, tricalcium aluminate, tricalcium oxide and silicate oxide